2000
DOI: 10.1007/s004420000464
|View full text |Cite
|
Sign up to set email alerts
|

Very high productivity of the C4 aquatic grass Echinochloa polystachya in the Amazon floodplain confirmed by net ecosystem CO2 flux measurements

Abstract: Fluxes of CO and HO vapour from dense stands of the C4 emergent macrophyte grass Echinochloa polystachya were measured by eddy covariance in both the low water (LW) and high water (HW, flooded) phases of the annual Amazon river cycle at Manaus, Brazil. Typical clear-sky midday CO uptake rates by the vegetation stand (including detritus, sediment or water surface) were 30 and 35 µmol CO (ground) ms in the LW and HW periods, respectively. A rectangular hyperbola model fitted the responses of "instantaneous" (20-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
3
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 30 publications
7
57
3
1
Order By: Relevance
“…3c,f). Both NEE raw and ER raw were depressed in the wet season relative to the dry season, and this pattern is opposite that found in other wetlands characterized by dry and wet seasons (Morison et al, 2000;Jones and Humphries, 2002 (Fig. 3d,e).…”
Section: Environmental Drivers Of Co 2 Exchangecontrasting
confidence: 81%
See 2 more Smart Citations
“…3c,f). Both NEE raw and ER raw were depressed in the wet season relative to the dry season, and this pattern is opposite that found in other wetlands characterized by dry and wet seasons (Morison et al, 2000;Jones and Humphries, 2002 (Fig. 3d,e).…”
Section: Environmental Drivers Of Co 2 Exchangecontrasting
confidence: 81%
“…Morison et al, 2000;Jones and Humphries, 2002). However, short-term data from these studies show NEE that is more than four times greater than the maximum values observed in this Everglades marsh (Fig.…”
Section: Annual Ecosystem Co 2 Exchangementioning
confidence: 66%
See 1 more Smart Citation
“…These negative correlations between NEE and PAR (or positive correlations between NEP and the intensity of available light) reveal an optimal adaptation of the plants to the environmental conditions created by the solar radiation, such as temperature, humidity and light. Similar negative correlations have been observed with EC by Morison et al (2000) for the C 4 aquatic grass Echinochloa polystachya of the Amazon and by Kathilankal et al (2008) for the Spartina alterniflora in a salt marsh on the eastern coast of Virginia. Using static chambers, Silva et al (2005) obtained the same results for Zostera noltii meadows in the intertidal flats of the Ria Formosa flat in Portugal.…”
Section: Relationship Between Low Tide Co 2 Fluxes and The Distributisupporting
confidence: 77%
“…The large proportion of autochthonous items consumed by P. flavipinnis reflects the high amount of fish and aquatic insects on its diet, which is probably related to the high productivity of the Central Amazonian floodplains (MORISON et al, 2000). Pellona flavipinnis may be classified as a generalist carnivorous species that feeds mainly on fishes and aquatic insects, according to prey availability.…”
Section: Discussionmentioning
confidence: 99%